Model-Based Control of Travelling Wave Type Ultrasonic Motors. - Maas, Jürgen; Schulte, Thomas; Grotstollen, H.; Fröhleke, Norbert
This paper gives a review of research activities at the Institute for Power Electronics and ElectricalDrives in Paderborn to the control of rotary travelling wave type ultrasonic motors. Based on a special designedhardware environment an advanced control scheme for inverter-fed travelling wave type ultrasonic motors is pre-sented. After several modelling steps, including an averaged model for the controller design, a speed control schemeis implemented on a prototype drive. It is realized as an outer control loop of an underlaid voltage and travellingbending wave vector controller. The novel speed control is using an inverse contact model by a neural network, inorder to compensate the nonlinear torque generation of the motor. The so equipped ultrasonic motor-drive meetsrequirements for applications in the field of servo-drives e.g. robotics. Since the reference values of the bendingwave control are calculated from the desired torque value by the neural network, open loop control of the drive´s torque is feasible, too.